"You have to believe the patient": What do people with fibromyalgia find helpful (and hindering) when accessing health care?. Issue 2 (30th July 2023) - Nishikawara, Ria K.; Schultz, Izabela Z.; Butterfield, Lee D.; Murray, John W.
ABSTRACT: Background: Fibromyalgia (FM) is a complex, still poorly understood, and difficult-to-treat chronic pain condition for which many people struggle to find adequate care. Aims: This study investigated the research question, "What do people accessing health care services for fibromyalgia perceive as helpful, hindering, and absent but desired?" with the aim of identifying clear, implementable changes for clinical practice. Materials and methods: This study used the enhanced critical incident technique (ECIT), a qualitative research method that focuses on helping, hindering, and desired factors, to explore the health care experiences of 14 individuals (12 women and 2 men) diagnosed with FM. Results: Using qualitative data analysis, results identified three categories of health care experiences: (1) systemic navigation, including financial and economic security; accessibility, flexibility, and continuity of care; and diversity of treatment options; (2) clinician–patient alliance, including invalidation and prejudice; therapeutic bond; and clinician–patient alignment on treatment plan; and (3) patient self-management strategies, including information-seeking and education, self-advocacy, social supports, symptom management strategies, and other coping strategies. Participants tended to conceptualize their health care concerns as a multilayered systemic problem. Conclusions: Participants described a medical system they perceived as poorly equipped to support their needs and tended to invalidate their health concerns. Helping experiences tended to be the result of unique efforts on the part of individual clinicians. Findings emphasize the importance of recognizing the complexities and psychological impact of pain, trusting clinician–patient relationships, multidisciplinary/interdisciplinary care within a biopsychosocial framework, and improved education and awareness around psychosocial aspects of FM and effective management of chronic pain.